O-219 Detailed morpho-kinetic analysis of the first cleavage can help in evaluating the viability of direct-cleaved human zygotes. (6th August 2021) - Shimura, T; Yumoto, K; Sugishima, M; Mio, Y
Abstract: Study question: Why do some direct-cleaved human zygotes still lead to a live birth? Summary answer: Direct-cleaved zygotes which have undergone the 2-cell stage can lead to a live birth, while zygotes cleaved from 1-cell to ≥ 3-cell do not. What is known already: In recent years, zygotes that develop from 2-cell to 3-cell within 5 hours after the first cleavage have been evaluated as "direct-cleaved" zygotes, because normal cleavage takes approximately 12 hours to complete. It was reported that their implantation rate was significantly lower than zygotes with normal cleavage pattern, and eliminating direct-cleaved zygotes from transfer could improve the implantation rate. However, some direct-cleaved zygotes at the first cleavage could still lead to a live birth. Few reports have examined the difference between a cleavage from 1-cell to ≥ 3-cell and 2-cell to ≥ 3-cell within 5 hours after the first cleavage. Study design, size, duration: A retrospective study involving 2, 077 cycles of IVF/ICSI between July 2012 and July 2019. A total of 5, 991 normally fertilized zygotes (2PN/2PB) were included. Of those, 3, 508 were evaluated as usable good/fair quality embryos on Day2/3, and the rest (n = 2, 483) were evaluated as poor quality and rejected from transfer or cryopreservation after 7 days of culture. Of 3, 508 usable embryos, 884 were selected based on the availability of results of live birth for this study. Participants/materials, setting, methods: Time-lapse imaging (5 slices along Z-axis every 10 minutes) was performed in EmbryoScopeTM. Zygotes were morphokinetically analyzed in detail and classified into four groups by their cleavage patterns: Group1 (1-cell→2-cell); Group 2 (1-cell→3-cell); Group 3 (1-cell→2-cell→≥3-cell within 5 hours after the first cleavage); and Group 4 (1-cell→2-cell→≥5-cell). The proportion, mean maternal age and live birth rate of each group were examined. Main results and the role of chance: The proportion of Groups 1-4 was 83.6% (n = 739), 3.8% (n = 34), 5.9% (n = 52), and 6.7% (n = 59), respectively. 0f 884 zygotes examined in this study, the mean maternal age was significantly higher in Group 2 and 4 than in Group 1 ( P < 0.05; 37.4±4.9 in Group1, 39.1±5.2 in Group 2, 38.6±6.0 in Group 3, and 38.7±5.1 in Group 4). The rate of confirmed gestational sac was significantly lower in Group 2 and 4 than in Group 1 [ P < 0.01; 36.3% (n = 268/739), 0% (n = 0/34), 25.0% (n = 13/52), and 18.6% (n = 11/59) in Groups 1-4, respectively]. Furthermore, the live birth rate was significantly higher in Group 1 than in Groups 2, 3 and 4 [ P < 0.01; 28.4% (n = 210/739), 0% (n = 0/34), 13.5% (n = 7/52), and 15.3% (n = 9/59) in Groups 1-4, respectively]. Above all, while zygotes in Group 2 showed no pregnancy and live birth at all, zygotes in Group 3 showed a live birth rate of 13.5%. However, they had a significantly higher miscarriage rate (42.9%, n = 6) compared to zygotes in Group 1 (19.5%, n = 55). Limitations, reasons for caution: It is very difficult to capture cleavage patterns by routine observations because the timings of developmental events are different between embryos. A time-lapse imaging and culturing system is essential to solve this problem, however, it cannot visualize the distribution of chromosomes, and no chromosomal analysis was conducted in this study. Wider implications of the findings: This study revealed that zygotes previously classified as "direct-cleaved" and eliminated from transfer included viable zygotes which could lead to a live birth. Therefore, it is crucial to optimize the use of time-lapse imaging of human zygotes in order to precisely evaluate the first cleavage. Trial registration number: not applicable